A continuum of admixture in the Western Hemisphere revealed by the African Diaspora genome - Rasika Ann Mathias (Nature Portfolio, 2016)
The Consortium on Asthma among African-ancestry Populations in the Americas (CAAPA) aims to better understand population genetics of the African diaspora. Here, it uses deeply sequenced whole-genomes to describe the impact of admixture and potential disease burden of deleterious variants.